2007
DOI: 10.4018/jeis.2007040105
|View full text |Cite
|
Sign up to set email alerts
|

The Digitization of an Aerospace Supply Network

Abstract: Unique , and certainly complex, networks of suppliers, clients, and operators (end users), characterize the supply chain in the aerospace manufacturing industry. With the emergence of e-commerce and enterprise information systems, a number of processes, locations, and partners can be linked globally-and in real time. Motivated by the need to achieve global integration, a Canadian aerospace manufacturer has embarked on a company-wide digitization initiative to integrate several members of its supply network. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Interviews with experts have been extensively used in the literature with regard to this industry, and numerous case studies have been done (Russell and Hoag 2004, Zsidisin and Smith 2005, Laframboise and Reyes 2007, Esposito and Passaro 2009. The focus group is one of the most widely used research tools in social sciences, and previous studies were found in the literature that use these in the area that concerns this study, operations management in general (Dey et al 2006, Binder andEdwards 2010) and SCM in particular (Oehmen et al 2010, Tate et al 2010.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interviews with experts have been extensively used in the literature with regard to this industry, and numerous case studies have been done (Russell and Hoag 2004, Zsidisin and Smith 2005, Laframboise and Reyes 2007, Esposito and Passaro 2009. The focus group is one of the most widely used research tools in social sciences, and previous studies were found in the literature that use these in the area that concerns this study, operations management in general (Dey et al 2006, Binder andEdwards 2010) and SCM in particular (Oehmen et al 2010, Tate et al 2010.…”
Section: Methodsmentioning
confidence: 97%
“…In this context, the aeronautics SC is gaining in complexity (Laframboise and Reyes 2007). Research studies are needed to improve the management of the new relationship established between the partners.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the improvement in Industry, Innovation, and Infrastructure (#9), the authors in [26] consider the aviation sector to be an enabler of the global integration process by implementing communications, strategic management, and advances in technology around the world with a close interface with all other components of the system. Given the interest in exploring the benefits of applying innovation and sustainable industrialization, a method for integrating a range of business practices into a common practice, merging process integration, quality management, and supply chain management, is shown in [27] for the Canadian aerospace manufacturer.…”
Section: The Sustainable Development Goals In the Aerospace Industrymentioning
confidence: 99%
“…The floating potential of the probe, V f , varied within a range of ±2 V. The electron contribution to the current appears abruptly, which indicates that the plasma is, as expected, relatively cold (T e ~ 1-2 eV). To estimate the density of electrons, Laframboise's theory of charge collection [17,18] was applied (see figure 8). ).…”
Section: 1probe Measurementsmentioning
confidence: 99%